El procedimiento en el juzgamiento de los delitos sexuales en contra de niños, niñas y adolescentes, frente al artículo 81 de la constitución de la república del Ecuador - Rita Madelin, Vásquez Veloz (2020)
ABSTRACT: In the present investigation work an analysis of the normative omission in which the National Assembly has incurred in not having included special procedures and expedited for children, adolescents and victims of sexual crimes, as established in article 81 of the Constitution, which has produced serious effects on this vulnerable group of society, because currently a child or adolescent who has been sexually violated undergoes the ordinary process, which in practice can take months and even years to complete. especially when appeals, appeals and review are presented. For this reason, the theoretical framework is found in Chapter I of the work, where the procedural stages of the ordinary procedure as well as the expedited procedure are analyzed. Similarly, the most common crimes committed against children and adolescents are identified; as well as the rights of children and adolescents victims of criminal offenses that are violated by not undergoing an expedited procedure. In Chapter II, there is the methodological framework in which are the research methods that were used in the development of this work as the synthetic analytic, which allows the identification and analysis of the most relevant norms of the proposed topic, as well The same is the discussion of results obtained in the field research, which serves as the basis for making the academic conclusions and recommendations made by the researcher.